Midwives' experience of their education, knowledge and practice around immersion in water for labour or birth - Lucy Lewis; Yvonne L. Hauck; Janice Butt; Chloe Western; Helen Overing; Corrinne Poletti; Jessica Priest; Dawn Hudd; Brooke Thomson (BMC, 2018)
Abstract Background There is limited research examining midwives' education, knowledge and practice around immersion in water for labour or birth. Our aim was to address this gap in evidence and build knowledge around this important topic. Methods This mixed method study was performed in two phases, between August and December 2016, in the birth centre of a tertiary public maternity hospital in Western Australia. Phase one utilised a cross sectional design to examine perceptions of education, knowledge and practice around immersion in water for labour or birth through a questionnaire. Phase two employed a qualitative descriptive design and focus groups to explore what midwives enjoyed about caring for women who labour or birth in water and the challenges midwives experienced with waterbirth. Frequency distributions were employed for quantitative data. Thematic analysis was undertaken to extract common themes from focus group transcripts. Results The majority (85%; 29 of 34) of midwives surveyed returned a questionnaire. Results from phase one confirmed that following training, 93% (27 of 29) of midwives felt equipped to facilitate waterbirth and the mean waterbirths required to facilitate confidence was seven. Midwives were confident caring for women in water during the first, second and third stage of labour and enjoyed facilitating water immersion for labour and birth. Finally, responses to labour and birth scenarios indicated midwives were practicing according to state-wide clinical guidance. Phase two included two focus groups of seven and five midwives. Exploration of what midwives enjoyed about caring for women who used water immersion revealed three themes: instinctive birthing; woman-centred atmosphere; and undisturbed space. Exploration of the challenges experienced with waterbirth revealed two themes: learning through reflection and facilities required to support waterbirth. Conclusions This research contributes to the growing knowledge base examining midwives' education, knowledge and practice around immersion in water for labour or birth. It also highlights the importance of exploring what immersion in water for labour and birth offers midwives, as this research suggests they are integral to sustaining waterbirth as an option for low risk women.